Optimalisasi Produktivitas Mesin Pencacah Sampah Organik Hasil Modifikasi - Aziz, Kholid; Sundari, Susanti; Irwanto, Sofyan; Yuspradana, Rizky; Nashiruddin, Muhammad (Fakultas Teknik Universitas Tulang Bawang, 2026)
Sustainable organic waste management is a crucial issue considering the serious negative impact of landfilling. Although organic waste has great potential to be processed into compost or eco-enzymes, small-scale conventional shredders often face obstacles such as low efficiency, monolithic structures, and reliance on the power grid, which hinder adoption at the communal level. This research aims to optimize the productivity of organic waste shredding machines with a capacity of 20 kg/hour through design modifications. The methodology applied is experiment-based Research and Development (R&D). The modifications made include the implementation of a modular design (dismantling) to overcome logistical constraints and the conversion of the drive system from an electric motor to a 6.5 HP gasoline motor to ensure independent operations at the site. Comparative performance evaluation was measured using the Marvin E. Mundel Productivity Model. The test results show a significant improvement in performance. The modified machine achieved a Productivity Index (IP) of 1,579, reflecting an increase in production effectiveness of 57.9%. This increase is also supported by processing time efficiency of 36.7%, reducing the enumeration time of 5 kg of waste to 19 minutes. In conclusion, design modification strategies that focus on adapting energy sources and improving mobility are very effective in producing appropriate technologies that are efficient and ready to be implemented in society. Keywords: Design Modification, Efficiency, Mundel Method, Productivity, Waste Shredder